Optimization of the Hydrolysis Process of Microalgae Porphyridium cruentum Biomass with Variations of Hydrochloric Acid Concentration, Temperature, and Time using Response Surface Methodology (RSM) - Alvita, Livia Rhea; Elsyana, Vida; Kining, Ekajayanti (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2023)
Microalgae Porphyridium cruentum has potential as a raw material for bioethanol production because it has a high carbohydrate content. These carbohydrates can be broken down into reducing sugars through the hydrolysis process. The reducing sugar obtained will be used as a substrate in the production of bioethanol. This study aimed to produce a substrate with the best-reducing sugar indicator and to determine the optimum conditions for hydrolysis of P. cruentum microalgae biomass following the Box-Behnken statistical experimental design, using Response Surface Methodology (RSM). The parameters of the optimized hydrolysis process were HCl concentration (2 - 0.2 N), temperature (60 -120 ˚C), and hydrolysis time (30-180 min). The optimum conditions that have been achieved using RSM are an HCl concentration of 1.91 N, a temperature of 60 °C, and a hydrolysis time of 180 min were predicted a maximum total reducing sugar production of 810 mg/L. The experimental result of total reducing sugar obtained at optimum conditions was 895 mg/L, which was well close to the predicted value, verifying the appropriateness of the model.Abstract is informed about the statements of the problem, methods, scientific finding results and conclusion concisely